INFLUENCE OF PRODUCT INNOVATION ON THE PERFORMANCE OF COFFEE COOPERATIVES IN KENYA - Kuguru, Peter; Jaensson, Jan-Erik; Nganga, Kinyanjui (European Journal of Business and Strategic Management, 2022)
Purpose: The purpose of the study was to assess the influence of product innovation on the performance of coffee cooperatives in Kenya. Methodology: A descriptive research design was applied. The target population of this study was 525 coffee cooperative societies in Kenya registered with the Commissioner for Cooperatives and licensed by AFFA (Coffee Directorate) as at 30th of October 2016. The sample size was 227 respondents. Structured questionnaires were used to collect primary data from the selected respondents. Findings: The results of the study revealed that product innovation and performance are positively and significantly related (Î²=0.631, p=0.002). This indicated that developments of new products are essential for the improvement of the coffee cooperatives' performance. Unique Contribution to Theory, Policy and Practice: The study recommended adoption of technology for the development of new services, new functions, and formation of new alliances. The study further recommended an organization to employ and develop a high technology for its product in order to determine strategic position to adopt the differentiation position or the cost leadership position. This study is recommended as it will benefit scholars and researchers who will gain insight on the influence of product innovation on performance of coffee co-operatives hence use it as a source of reference for other researches. The results of this study will contribute new knowledge which will provide the government and other stakeholders with better ways of managing co-operatives and improving their production.